Expert and Clinical Assessment of the Quality of Dental Care in the Context of Digitalization of Medical Documentation - Boyko, М. А.; Varfolomeyev, Є. А.; Mykolaichuk, С. І. (Actual Dentistry, 2025)
Actuality: Identifying defects in medical care within dental practices often necessitates a forensic medical examination. This process relies on, among other factors, a comprehensive review of medical documentation by specialists. Research and analysis of the capabilities of contemporary medical information systems utilized in dentistry may illuminate the synchronization of quality assurance processes in dental care delivery. Goal: To identify the peculiarities of conducting forensic medical evaluations of dental care and explore promising ways to improve the quality of such evaluations. Materials and methods: Annual reports of forensic medical bureaus in Ukraine for the years 2017–2022, as well as a sample of 798 commission forensic medical examinations conducted at the Forensic Medical Department of the State Institution “Main Bureau of Forensic Medical Expertise of the Ministry of Health of Ukraine” from 2012 to 2023 regarding defects in medical care delivery. Results: The number of forensic medical examinations related to dental care performed in Ukrainian forensic medical bureaus between 2017 and 2021 ranged from 13 examinations in 2017 to 23 examinations in 2020, accounting for 2.3–4.26% of the total number of forensic medical examinations. In 2022, only six examinations related to dental care were conducted in regional forensic medical bureaus, comprising 1.9% of the total number of “medical malpractice” cases. A trend was observed toward an increase in the relative number of such examinations, from 3.3% in 2012 to 4.7% in 2019, indicating the growing relevance of this field. Defects in medical care were identified in 79.4% of these cases. Among these defects, 78.3% showed a direct causal relationship between deficiencies in medical care and adverse outcomes. An essential aspect of the qualitative evaluation of dental care is the ability to examine electronic dental records containing patient treatment data during forensic assessments. A specialized CRM system for managing dental clinics is optimal for private clinics with moderate workloads. In contrast, the Helsi system is more suitable for state-owned medical institutions focused on high standards of digitalization, although it requires profile-specific enhancements similar to specialized CRM systems. Conclusions: The number of forensic medical examinations concerning dental care during the analyzed period was relatively small, ranging from 1.9% to 4.7% of the total number of forensic examinations. Defects in medical care were found in 79.4% of the examined cases. In many cases, the lack of sufficient medical documentation prevented the conduct of forensic medical examinations regarding the quality of dental care. The most promising tools are digital electronic databases (integrated dental clinic management systems), the analysis and study of which enable detailed tracking of the quality and completeness of dental care at different stages of treatment. However, studying electronic dental databases during forensic examinations faces mainly technical and legal challenges, such as the lack of clear procedures for seizure digital medical records by law enforcement agencies and the prevention of data modification and falsification.